Public Health For The 21st Century. - Orme, Judy (McGraw-Hill International (UK) Ltd., 2007)
Analyses and reflects upon the influence of history, research and procedures upon contemporary public health practice. This book explores the debates surrounding the meaning of public health and looks at the policy changes that are reshaping its context. It examines the contributions that epidemiology and health economics make to public health.